Development of a coumarin-based fluorescent probe for hydrogen peroxide based on the Payne/Dakin tandem reaction. (June 2021) - Wu, Fangfang; Yu, Hanjie; Wang, Qin; Zhang, Jianjian; Li, Zheng; Yang, Xiao-Feng
Abstract: Hydrogen peroxide (H2 O2 ) is associated with many physiological and pathological processes in biological systems. Here, we report 7-diethylamino-3-formyl-coumarin (Cou-CHO ) as a turn-on fluorescent probe for H2 O2 . The proposed probe employs a tandem Payne/Dakin reaction to convert the electron-withdrawing aldehyde to the electron-donating hydroxyl group, thus hindering the formation of twisted intramolecular charge transfer (TICT) state of 7-diethylaminocoumarin, and thereby resulting in a fluorescence turn-on response. Cou-CHO features high specificity, excellent sensitivity and fast response toward H2 O2 . In particular, Cou-CHO enables the direct visualization of basal and endogenously produced H2 O2 in living cells. The results demonstrate that the tandem Payne/Dakin reaction can provide a new choice to develop H2 O2 -selective probes. Graphical abstract: Image 1 Highlights: A coumarin-based fluorescent probe for hydrogen peroxide is proposed. The present probe employs a tandem Payne/Dakin reaction to convert the aldehyde to the corresponding hydroxyl group. The turn-on fluorescence response is due to hindering formation of twisted intramolecular charge transfer state of 7-diethylaminocoumarin. The probe enables the direct visualization of endogenous hydrogen peroxide in living cells.